Anionic redox reaction triggered by trivalent Al3+ in P3-Na0.65Mn0.5Al0.5O2. Issue 23 (25th February 2021) - Shi, Ding-Ren; Wang, Tian; Shadike, Zulipiya; Ma, Lu; Yang, Xiao-Qing; Chu, Shu-Fen; Zhao, Zhi-Wei; Peng, Zhang-Quan; Fu, Zheng-Wen
Abstract : P3-type Na0.65 Mn0.5 Al0.5 O2 (NMAO) exhibits a first charging capacity of ∼110 mA h g −1 with oxygen redox behavior triggered by Al 3+ . Abstract : P3-Na0.65 Mn0.5 Al0.5 O2 (NMAO) has been synthesized and studied as a cathode for sodium batteries, and shows anionic redox reaction (ARR) and exhibits a first charging capacity of ∼110 mA h g −1 . The electrochemical mechanism of NMAO was comprehensively investigated by X-ray absorption spectroscopy (XAS), X-ray photoelectron spectroscopy (XPS), Raman spectroscopy, and density functional theory (DFT) calculations. The reversible oxygen redox behaviour is triggered by Al 3+ through oxygen quasi non-bonding states generated by the relatively ionic interaction of Al and O. Furthermore, the presence of Al 3+ can suppress oxygen loss in ARR. This work provides new insights into the design and mechanism of anionic redox active cathode materials.